TINJAUAN YURIDIS FUNGSI PENYELIDIKAN DAN PENYIDIKAN TINDAK PIDANA PENGANIAYAAN DI POLSEK KASIHAN - SIGIT, HENDRO PURNOMO (Dinamika Hukum, 2016)
The purpose of this study was to examine what forms the duties and functions of police in conducting investigations and inquiries general crime, especially the crime of persecution, and to find out what barriers or constraints Police on the ground in the investigation and the investigation of particular criminal acts of persecution. Background Research that there are technical differences in the process of inquiry and investigation conducted so far by the police. Methods The study consisted of the kind of research; nature of the research; where research; population; engineering / means of data collection; data analysis method. Results showed the investigation was based on a report or complaint someone on the occurrence of an event of a violation or crime. From these reports are recorded in a register / Letter of Acceptance Report. According to the report, police conducted an investigation. From the results of the investigation if it found violations or crimes, then the examination process increased to the investigation. The process to find sufficient evidence and find the suspect. However, if such act is not a crime, the examination is stopped and by the investigator issued Warrant Termination of Investigation (SP3). Obstacles encountered in the field is the lack of police personnel and the ability of investigators. Moreover, investigators and investigators in the Police Sector Kasihan conducted by the same police officer. Keywords: Research, investigation and persecution.